El Segrià i la Franja d'Aragó. A literary cartography of the border from the works of Francesc Serés - Ballonga i Montoliu, Adria (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
This article aims to address the representation of the Catalan-Aragonese border space present in Francesc Serés’ novels Una llengua de plom and La pell de la frontera. Choosing the border as a literary object as well as a subject, the author displays an intimate geography aiming to subvert the dichotomy between center and periphery. From the margins, Serés turns his writing into an anthropological, historical and literary document that deals with various subjects such as the loss of rurality, the death of nature, or landscape as ruin.
Keywords: border; Francesc Serés; ecology; anti-landscape; historic materialism